2021
DOI: 10.1590/0001-3765202120191120
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Environmental Management and Planning based on Soil Erosion Susceptibility Scenarios

Abstract: This article presents the identifi cation of soil use potential for different agropastoral and forest scenarios, using an indicator for erosion susceptibility from the spatialized Universal Soil Loss Equation (USLE). All USLE factors were spatialized using ArcGis 10.5 software, for the case study of the Cachoeira Cinco Veados Watershed-RS. To determine the R factor, we used the Cassol et al. 2007 equation and a 33-year series of rain data from six climatic stations. For the K factor, published values for the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…As Calzolari et al (2020) concluded, it is necessary to contribute to generating social and political awareness about the role of soil in the built environment and providing tools to assess and map the ecosystem services of soils and favour their integration, even preferentially in certain geographical contexts, in planning processes. In turn, Weiler et al (2021), beyond focusing essentially on the susceptibility to soil erosion in certain areas and under specific physical‐environmental conditions, argued that the results and, more specifically, their resulting maps, constitute suitable instruments for land‐use planning (and therefore, we understand, for territorial planning by extrapolation). Therefore, we consider that, for these purposes, an ad hoc operational model as presented here, and a discussion on its relevance and the added value of the mentioned evaluation framework, must be key for land managers and territorial policymakers.…”
Section: Resultsmentioning
confidence: 99%
“…As Calzolari et al (2020) concluded, it is necessary to contribute to generating social and political awareness about the role of soil in the built environment and providing tools to assess and map the ecosystem services of soils and favour their integration, even preferentially in certain geographical contexts, in planning processes. In turn, Weiler et al (2021), beyond focusing essentially on the susceptibility to soil erosion in certain areas and under specific physical‐environmental conditions, argued that the results and, more specifically, their resulting maps, constitute suitable instruments for land‐use planning (and therefore, we understand, for territorial planning by extrapolation). Therefore, we consider that, for these purposes, an ad hoc operational model as presented here, and a discussion on its relevance and the added value of the mentioned evaluation framework, must be key for land managers and territorial policymakers.…”
Section: Resultsmentioning
confidence: 99%